DINAMIKA RESILIENSI MATEMATIS MAHASISWA DALAM PEMBELAJARAN GAMIFICATION (WORDWALL & QUIZIZZ): MENGUNGKAP SISI AFEKTIF DI BALIK SKOR DIGITAL - Ayu Silvi Lisvian Sari; Cicik Pramesti; Riki Suliana Ranggawati Sidik; Suryanti Suryanti (Inteligensi : Jurnal Ilmu Pendidikan, 2025)
The integration of gamification platforms like Wordwall and Quizizz in higher education mathematics is often evaluated based on cognitive outcomes. However, the affective dimension, specifically mathematical resilience, remains under-explored. This qualitative research investigates the dynamics of students' mathematical resilience during gamified learning. The study involved 17 Mathematics Education students from Universitas PGRI Adi Buana PSDKU Blitar. Data were collected through participant observation, score documentation, and in-depth interviews. The thematic analysis revealed three main themes: (1) "Adrenaline Rush vs. Mental Block," where timer features triggered anxiety in students with low resilience; (2) "Leaderboard Effect," where public ranking negatively impacted self-esteem for lower-ranked students; and (3) Coping Strategies, distinguishing resilient students who used failure for self-evaluation from those who resorted to random guessing. The study concludes that high digital scores do not necessarily reflect psychological comfort. Future instruction must balance competitive elements with affective scaffolding to foster true mathematical resilience.